Pekerja bermasalah : Hubungan antara persepsi masalah, tindakan dan kesan terhadap prestasi pekerja dan jabatan - Ismail, Zakaria; Omar, Abdullah; Yahya, Khulida Kirana (Sekolah Pengurusan, Universiti Utara Malaysia, 2003)
In an organization, the existence of marginal employees may be negligible in terms of their numbers. However, their issues need to be carefully handled because failing to do so may warrant its serious impacts on the level of performance of the employees concerned and may as well implicate on other employees’ motivation and performance at a larger scale or at organizational wide. This would demand a considerable amount of managers’ time and efforts to specially attend to those cases. And in so doing, it would unnecessarily be constraining the managers' attention on other critical and more strategic management functions. Hence, this study intends to assess the relationship between types of marginal employees, as being perceived by the managers and their remedial actions and the consequent efects of those actions on the individual employees and departmental performance. Basically, this study assess four perceived types of marginal employees, which are employees who are associated with performance-related problems, attitudinal-related issues, serious misconducts and lack of self-disciplined. As for the remedial actions that the managers may at their prerogative meted them out, this study has identified three major types, including verbal advice, written warning and termination of service or dismissal. The findings of the study reveal that problems that are perceived as not serious are being dealt with relatively less severe actions by the managers. Likewise, for serious cases involving misconducts for instance, may warrant severe actions. Generally, each remedial action taken by the managers on the individual marginal employee has resulted in positive aggregate effects on the overall departmental performance. However, there are no significant correlations between the remedial actions taken by the managers and the level of performance and commitment of the individual employee.